Pengaruh upah, pertumbuhan ekonomi dan kesempatan kerja terhadap jumlah pengangguran terdidik di Kabupaten Muaro Jambi Tahun 2001-2015 - Depi, Depi; Yulmardi, Yulmardi; Hardiani, Hardiani (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
This research aims to analyze the effect of wages, economic growth, and employment against the number of Educated Unemployment in Muaro Jambi Regency period 2001-2015. This research is a quantitative research using time series data from the years 2001-2015. The type of data used in this research is secondary data obtained from the Badan Pusat Statistik of Jambi Province. The results showed that the wages and employment opportunities have a significant influence on the number of educated unemployment in Muaro Jambi Regency, but economic growth has not significantly influenced the number of educated unemployment in Muaro Jambi Regency years 2001-2015. The regression results show that the value of RÂ² the independent variable (wages, economic growth, and employment opportunities) has a value of 0,627091 which means 62,70 % number of educated unemployment affected by wages, economic growth, and employment opportunities. While remaining 37,30 % explained by variables other than the model.